Effect of job satisfaction on employee performance with motivation as a moderating variable at Sekolah Menengah Kerjuruan Swasta (SMKS) Ki Hajar Dewantoro Tangerang City using the Structural Equation Modeling (SEM) method - Aryata, I Made; Marendra , I Gede (Enrichment : Journal of Management, 2024)
SMKS Ki Hajar Dewantoro was established in 1986 located at Tangerang City. Maintaining the quality of education is the biggest challenge for every school in Indonesia where there are around 127 Vocational Schools in Tangerang City that have the potential to become competitors. Based on data from 2018 to 2021 there is a decrease in employee performance of 15% when compared to 2018, where employee performance in 2021 is 70%. Job satisfaction is a factor that influences employee performance, according to Endra (2021) states that job satisfaction has a significant effect on employee performance. On the other hand, motivation from 2018 to 2021 is known to have decreased employee motivation by 19% when compared to 2018 where employee motivation was only 65%. Based on these problems, it is known that there has been a decrease in employee performance in 2021 by 15%. Based on the calculation results using the Structural Equation Modeling (SEM) method, it can be concluded that a) job satisfaction has no effect on employee performance; b) Motivation has no effect on Employee Performance; and c) Motivation as a moderating variable strengthens the effect of Job Satisfaction on Employee Performance with a p-value of 0.028.